2019
DOI: 10.35530/it.070.02.1592
|View full text |Cite
|
Sign up to set email alerts
|

Designing the functional garments for people with physical disabilities or kyphosis by using computer simulation techniques

Abstract: Proiectarea îmbrăcămintei funcționale pentru persoanele cu dizabilități fizice sau cifoză prin utilizarea tehnicilor de simulare pe calculator Obiectivul dublu al acestui studiu este de a documenta provocările actuale ale tehnicilor de scanare 3D și de simulare pe calculator pentru dezvoltarea de articole de îmbrăcăminte funcționale pentru persoanele cu dizabilități fizice sau cifoză posturală. Prima parte a studiului investighează problemele de sănătate ale utilizatorilor de scaune cu rotile și prezintă posib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
1
7
0
Order By: Relevance
“…Four properties, which characterize surfaces similar as colours in colour space [23], where each colour is represented as a mix of values L*, a* and b*. The surface's geometrical space consists of these four properties: Curvature -C, Acceleration -A, Symmetry -S and Proportionality -P. In addition, it was found out that CASP methodology is suitable for the purpose of analysis of the deformed areas of a human's body and adapted garment's pattern design for people with scoliosis and kyphosis [13][14][15]. In this research, the CASP methodology was applied on real bodies with spine deformity, mainly to evaluate the degree of curvature and symmetry of the upper spine or the roundback.…”
Section: Casp Methodology To Study Teenagers and Adults' Upper Backmentioning
confidence: 99%
See 1 more Smart Citation
“…Four properties, which characterize surfaces similar as colours in colour space [23], where each colour is represented as a mix of values L*, a* and b*. The surface's geometrical space consists of these four properties: Curvature -C, Acceleration -A, Symmetry -S and Proportionality -P. In addition, it was found out that CASP methodology is suitable for the purpose of analysis of the deformed areas of a human's body and adapted garment's pattern design for people with scoliosis and kyphosis [13][14][15]. In this research, the CASP methodology was applied on real bodies with spine deformity, mainly to evaluate the degree of curvature and symmetry of the upper spine or the roundback.…”
Section: Casp Methodology To Study Teenagers and Adults' Upper Backmentioning
confidence: 99%
“…The results obtain by applying CASP methodology on theoretical case studies showed, that this methodology could be adequate for assuring the appropriate garment pattern design for real persons with curved kyphosis [13][14][15]. The main aim of this research is to investigate the applicability of the CASP (Curvature, Acceleration, Symmetry, Proportionality) methodology for adapted garments' pattern design for real cases of adults and teenagers with spine deformity.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, production logistics as well as information and communication technologies have gained importance, in order to keep job functions requiring higher qualifications within Europe [1][2][3]. Clothing products and safety equipment are ideal for personalization and customization according to consumer requirements, which do not fit into standard sizes (body size and atypical conformations or special requirements) and are an important niche for the garments sector [4][5][6][7]. The current paper presents the innovative concept for personalized pattern design of safety equipment applied within SC MATEI CONF GRUP SRL, highlighting the importance of personalization and its competitive advantages, from the idea to the prototype or product and testing it.…”
Section: Introductionmentioning
confidence: 99%
“…The continuous development of the IT sector in general has influenced the quality of life. The innovative products in the textile industry propose solutions with incidence on certain areas like medicine [1] in putting forward new ways to design and produce virtual prototypes of garments adapted for people with scoliosis [2], other impairments [3] and fashion like the design of a three dimensional virtual apparel online application web page [4] or the use of 3D surface geometry for modelling and simulation purposes [5]. Due to the great development of the smartphones in recent years it has become a habit for us all to have a powerful computer in our pocket.…”
Section: Introductionmentioning
confidence: 99%